A method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates

Through various technical means, the problem of the problem of the existing technology being unable to effectively identify aggregates that cause hardened concrete or mortar self-disintegration, and the effective evaluation and protection of the safety and stability of concrete structures is achieved.

CN114720498BActive Publication Date: 2025-03-07ANHUI & HUAI RIVER WATER RESOURCES RES INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210369470.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-09
Publication Date
2025-03-07
Estimated Expiration
2042-04-09

AI Technical Summary

Technical Problem

The prior art cannot effectively detect and analyze the problematic aggregates that cause self-disintegration of hardened concrete or mortar, resulting in damage to the safety and appearance of concrete structures.

Method used

The chemical composition, phase and microstructure of the problematic aggregate are analyzed by on-site sampling, indoor tests, X-ray fluorescence spectroscopy analysis, simulation tests in specific environments, X-ray diffraction tests, scanning electron microscopy tests, etc., to determine the degree of impact on the engineering entity, and to provide treatment protection suggestions.

Benefits of technology

Through detailed inspection and analysis, the problematic aggregates that cause self-disintegration of hardened concrete or mortar can be accurately identified, their impact on the engineering entity can be evaluated, and effective treatment protection measures can be provided to improve the safety and stability of concrete structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005226593300000031
    Figure FDA0005226593300000031
Patent Text Reader

Abstract

A method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates belongs to the detection method of building materials. After on-site sampling, indoor tests, X-ray fluorescence spectrum analysis tests, simulation tests under specific environments, X-ray diffraction tests, and scanning electron microscope tests are performed to analyze the degree of influence of the problematic aggregates, and finally the treatment and protection measures are verified. The present invention analyzes the chemical composition, physical phase, microstructure, etc. of the self-collapsed part of the concrete surface and the suspected problematic aggregates inside the concrete, finds out the unreacted problematic aggregates, and identifies what the problematic aggregates are, identifies the source of the problematic aggregates in combination with the actual situation, analyzes the process, environment, and mechanism of the self-collapse phenomenon, determines the degree of influence of the problematic aggregates on the engineering entity, and gives reasonable treatment and protection suggestions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building material detection methods, and in particular to the technical field of methods for detecting and analyzing self-collapse of hardened concrete or mortar caused by problematic aggregates. Background Art

[0002] With the development and progress of society, people build a large number of concrete structures every year, resulting in a great demand for "aggregates", the main component of concrete. People are also accustomed to easily obtaining aggregates directly from nature. As the country attaches importance to ecological environmental protection, the mining of aggregates for concrete or mortar is subject to increasingly strict restrictions. Some aggregates that were originally not suitable for concrete or mortar are intentionally or unintentionally used in production, causing the phenomenon of self-collapse of hardened concrete or mortar to increase year by year, causing great damage to the safety and appearance of concrete structures, and triggering many social conflicts. At present, there is no set of detection and analysis methods for this phenomenon in China. Summary of the invention

[0003] The present invention provides a method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates, analyzes the problematic aggregates that cause the self-collapse of hardened concrete or mortar, further determines the degree of influence of the problematic aggregates on the engineering entity, and gives reasonable treatment and protection suggestions.

[0004] The specific technical solutions are as follows:

[0005] A method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates, comprising the following steps:

[0006] Step 1: On-site sampling;

[0007] Step 2: Indoor test;

[0008] Step 3: X-ray fluorescence spectrometry analysis test;

[0009] Step 4: Simulation test under specific environment;

[0010] Step 5: X-ray diffraction test;

[0011] Step 6: Scanning electron microscope test;

[0012] Step 7: Analysis of the impact of problematic aggregates;

[0013] Step 8: Verify the handling and protection measures.

[0014] Preferably, the specific process of on-site sampling in step 1 of the present invention is:

[0015] Take samples from the collapsed parts by core drilling or cutting. Before coring or cutting, the collapsed parts of hardened concrete or mortar should be sealed and protected; or the suspicious granular or powdery materials in the collapsed parts should be peeled off on site; the removed core samples or test blocks should be marked and photographed.

[0016] Preferably, the specific process of the indoor test in step 2 of the present invention is:

[0017] The size of the self-collapsed part on the retrieved core sample was measured and photographed, and it was mixed with the suspected material causing the self-collapsed part extracted on site, ground and passed through a 0.075mm square hole sieve to obtain sample 1.

[0018] Preferably, the specific process of the X-ray fluorescence spectrometry analysis test in step 3 of the present invention is:

[0019] Perform an X-ray fluorescence spectrum analysis test on sample 1, and record the result as fluorescence 1; cut part of the retrieved concrete core sample into 1 cm thick slices or cut part of the retrieved mortar test block into 1 cm wide strips, and perform an X-ray fluorescence spectrum analysis test on the suspected aggregate position in the cut surface, compare the result with fluorescence 1, and record the similar result as fluorescence 0, and mark it with a marker pen;

[0020] Randomly take three concrete core samples or mortar test blocks, make the core samples or test blocks into particles with the help of a press and / or a hammer, pick out the problematic aggregates that will cause the hardened concrete or mortar to collapse on its own, and do an X-ray fluorescence spectrometry test. Put the aggregates with results similar to Fluorescence 1 together, crush and grind them, and pass them through a 0.075mm square hole sieve to obtain Sample 2, do an X-ray fluorescence spectrometry test, and the result is recorded as Fluorescence 2.

[0021] Preferably, the specific process of the simulation test under a specific environment in step 4 of the present invention is:

[0022] Place the sheet or strip specimen that has been subjected to X-ray fluorescence spectrometry analysis in a water bath and heat to boiling. Keep boiling for 6 hours and then cool naturally to room temperature. Observe the marking points and overall damage of the specimen after boiling, take photos and record them. After placing them in a natural drying state, conduct X-ray fluorescence spectrometry analysis on the material at the damaged point again. If there is no damaged point, it is not necessary to do it, and the result is recorded as fluorescence 0-0.

[0023] Compare and analyze the relationship between fluorescence 0 and fluorescence 0-0, fluorescence 2 and fluorescence 1, fluorescence 0-0 and fluorescence 1, determine and find out the problematic aggregate that has not reacted, and record and analyze the self-collapse of aggregate at the identified point.

[0024] Preferably, the specific process of the X-ray diffraction test in step 5 of the present invention is:

[0025] X-ray diffraction tests were carried out on sample 1 and sample 2 respectively, and the results were XRD1 and XRD2 respectively. The relationship between the two and the process of mutual transformation were analyzed.

[0026] Preferably, the specific process of the scanning electron microscope test in step 6 of the present invention is:

[0027] SEM tests were conducted on the suspected reacted materials and unreacted suspected problematic aggregates at the collapse site to verify the X-ray diffraction analysis test results from the microscopic morphology.

[0028] Preferably, the specific process of analyzing the impact degree of problematic aggregate in step seven of the present invention is:

[0029] 16 core samples or test blocks were randomly selected, of which 10 core samples or test blocks were cut into two 10mm thick sheets or 10mm wide strips without appearance defects, a total of 20 test pieces, all of which were photographed for appearance; the remaining 6 core samples or test blocks were subjected to compressive strength tests, of which 3 were used as comparison test pieces;

[0030] Put 3 core samples or test blocks and 20 test pieces into a water bath and heat them to boiling. After boiling for 6 hours, cool them naturally to room temperature. After leaving them to dry naturally, test and compare the compressive strength of the samples. And the compressive strength of the test specimens ,

[0031] Formula (1)

[0032] Formula (2)

[0033] According to formula (1), the change rate of compressive strength before and after the test is calculated. ; Carry out appearance inspection and take photos, compare with the photos before the test, and count the number of damaged specimens after boiling of 20 specimens , calculate the self-collapse failure rate of the problematic aggregate according to formula (2): ; The compressive strength change rate before and after the test and the self-collapse failure rate of problematic aggregates It serves as the basis for judging the influence of problematic aggregate on hardened concrete or mortar.

[0034] Preferably, the specific process of processing the protection measure verification in step eight of the present invention is:

[0035] Take 18 core samples or strip test blocks from the core samples or test blocks retrieved from the site, put them into test box respectively, and place them in six environments for testing: naturally dry and isolated from air, naturally dry and in contact with air, moist surface and isolated from air, moist surface and in contact with air, saturated with water and isolated from air, and saturated with water and in contact with air, with 3 test pieces in each environment. Then put the test piece box into a water bath, raise the temperature from room temperature to 100±2℃, boil it for 6 hours, and then cool it naturally to room temperature. Check and record the damage of the test pieces in each environment, and judge which environment is most beneficial and most harmful to keeping the test pieces in good condition according to the damage of the test pieces, so as to give more reasonable treatment and protection suggestions.

[0036] Compared with the prior art, the present invention adopts the above technical scheme: by analyzing the chemical composition, physical phase, microstructure and other aspects of the self-collapsed parts of the concrete surface and the suspected problematic aggregates inside the concrete, the unreacted problematic aggregates are found and the problematic aggregates are identified. The sources of the problematic aggregates are identified based on the actual situation, the process, environment and mechanism of the self-collapse phenomenon are analyzed, the degree of influence of the problematic aggregates on the engineering entity is determined, and reasonable treatment and protection suggestions are given. DETAILED DESCRIPTION

[0037] A method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates, comprising the following steps:

[0038] Step 1: On-site sampling:

[0039] (1) For the collapsed part, the core drilling method or cutting method is used to take samples. In order to reduce the contamination of suspicious objects (mainly dust and water) during core sampling or cutting, the collapsed part of hardened concrete or mortar needs to be sealed and protected before core sampling or cutting. When using the core drilling method, it is recommended that the core sample diameter is 70mm, the core is taken on the concrete slab, the depth is the slab thickness, and the steel bars should be avoided. When using the cutting method, the recommended cutting size for sampling is: length × width = 100mm × 100mm.

[0040] (2) Peel off suspicious granular or powdery materials in the collapsed area on site. When sampling, record the sampling location and take photos, then mark and photograph the removed core samples or test blocks.

[0041] Step 2: Indoor test:

[0042] The dimensions (length, width and depth) of the self-collapsed part on the retrieved core sample were measured and photographed, and the sample was mixed with the suspected material causing the self-collapsed part extracted on site, ground and passed through a 0.075mm square hole sieve to obtain sample 1.

[0043] Step 3: X-ray fluorescence spectrometry analysis test:

[0044] Perform an X-ray fluorescence spectrum analysis test on sample 1, and record the result as fluorescence 1; cut part of the retrieved concrete core sample into 1 cm thick slices or cut part of the retrieved mortar test block into 1 cm wide strips, and perform an X-ray fluorescence spectrum analysis test on the suspected aggregate position in the cut surface, compare the result with fluorescence 1, and record the similar result as fluorescence 0, and mark it with a marker pen;

[0045] Randomly take three concrete core samples or mortar test blocks, make the core samples or test blocks into particles with the help of a press and / or a hammer, pick out the problematic aggregates that may cause the self-collapse of hardened concrete or mortar, and do an X-ray fluorescence spectrometry test. Put the aggregates with similar results to Fluorescence 1 together, crush and grind them, and pass them through a 0.075mm square hole sieve to obtain sample 2, do an X-ray fluorescence spectrometry test, and the result is recorded as Fluorescence 2.

[0046] Step 4: Simulation test under specific environment:

[0047] The test was conducted in accordance with the method of "Detection and inference of potential hazards of free calcium oxide" in Appendix G of the "Technical Standard for Building Structure Inspection" (GB / T50344-2019). The sheet or strip specimens that have been subjected to the X-ray fluorescence spectrometry test were placed in a water bath and heated to boiling. After boiling for 6 hours, they were naturally cooled to room temperature. Observe the marking points and overall damage of the specimens after boiling, take photos and record them, and after placing them in a naturally dry state, conduct the X-ray fluorescence spectrometry test on the substances in the damaged points again. If there is no damage point, it can be omitted, and the result is recorded as fluorescence 0-0.

[0048] Compare and analyze the relationship between fluorescence 0 and fluorescence 0-0, fluorescence 2 and fluorescence 1, fluorescence 0-0 and fluorescence 1, determine and find out the problematic aggregate that has not reacted, and record and analyze the self-collapse of aggregate at the identified point.

[0049] Step 5: X-ray diffraction test:

[0050] X-ray diffraction tests were carried out on sample 1 and sample 2 respectively, and the results were XRD1 and XRD2 respectively. The relationship between the two and the process of mutual transformation were analyzed.

[0051] Step 6: Scanning electron microscope test:

[0052] SEM tests were conducted on the suspected reacted materials and unreacted suspected problematic aggregates at the collapse site to verify the X-ray diffraction analysis test results from the microscopic morphology.

[0053] Step 7: Analysis of the impact of problematic aggregates:

[0054] 16 core samples or test blocks were randomly selected, and two 10mm thick sheets or 10mm wide strips without appearance defects were cut from 10 core samples or test blocks, totaling 20 test pieces, all of which were photographed for appearance. Six core samples or test blocks were subjected to compressive strength tests (three of which were used as comparison test pieces), concrete core samples were subjected to compressive strength tests in accordance with the Technical Specification for Testing Concrete Strength by Core Drilling Method JGJ / T384-2016, and mortar test blocks were subjected to compressive strength tests in accordance with the Technical Specification for Testing the Compressive Strength of Hardened Mortar by Impact Method YB9248-1992.

[0055] Place 3 core samples or test blocks and 20 test pieces in a water bath and heat to boiling. Keep boiling for 6 hours and then cool naturally to room temperature. After leaving it to dry naturally for at least 3 days, test the compressive strength of the samples. And the compressive strength of the test specimens ,

[0056] Formula (1)

[0057] Formula (2)

[0058] According to formula (1), the change rate of compressive strength before and after the test is calculated. ; Carry out appearance inspection and take photos, compare with the photos before the test, and count the number of damaged specimens after boiling of 20 specimens , calculate the self-collapse failure rate of the problematic aggregate according to formula (2): ; The compressive strength change rate before and after the test and the self-collapse failure rate of problematic aggregates It serves as the basis for judging the influence of problematic aggregate on hardened concrete or mortar.

[0059] Step 8: Verification of processing protection measures:

[0060] According to the mechanism of self-collapse, it is simulated whether hardened concrete or mortar can produce self-collapse in different environments, so as to determine the influence of the environment (mainly water and air) on the self-collapse of hardened concrete or mortar, and give reasonable treatment and protection measures accordingly.

[0061] Take 18 core samples (recommended diameter 25mm) or strip test blocks (recommended width 20mm) from the core samples or test blocks retrieved from the site, put them into test boxes, and place them in six environments: naturally dry and isolated from air, naturally dry and in contact with air, moist surface and isolated from air, moist surface and in contact with air, saturated with water and isolated from air, and saturated with water and in contact with air for testing, with 3 test pieces in each environment. Then put the test piece box into a water bath, raise the temperature from room temperature to 100±2℃, boil it for 6 hours, and then cool it naturally to room temperature. Check and record the damage of the test pieces in each environment, and judge which environment is most beneficial and most harmful to keeping the test pieces in good condition according to the damage of the test pieces, so as to give more reasonable treatment and protection suggestions.

[0062] The present invention analyzes the chemical composition, physical phase, microstructure and other aspects of the self-collapsed areas on the concrete surface and the suspected problem aggregates inside the concrete to find out the unreacted problem aggregates and distinguish what the problem aggregates are. The source of the problem aggregates is determined based on actual conditions, the process, environment and mechanism of the self-collapse phenomenon are analyzed, the degree of influence of the problem aggregates on the engineering entity is determined, and reasonable treatment and protection suggestions are given.

Claims

1. A method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates, characterized in that The steps include: Step 1: On-site sampling; Step 2: Indoor test; the specific process is: The size of the self-collapsed part on the retrieved core sample was measured and photographed, and it was mixed with the suspected material causing the self-collapsed part extracted on site, ground and passed through a 0.075mm square hole sieve to obtain sample 1; Step 3: X-ray fluorescence spectrometry analysis test; the specific process is as follows: Perform an X-ray fluorescence spectrum analysis test on sample 1, and record the result as fluorescence 1; cut part of the retrieved concrete core sample into 1 cm thick slices or cut part of the retrieved mortar test block into 1 cm wide strips, and perform an X-ray fluorescence spectrum analysis test on the suspected aggregate position in the cut surface, compare the result with fluorescence 1, and record the similar result as fluorescence 0, and mark it with a marker pen; Randomly take three concrete core samples or mortar test blocks, make them into granules, pick out the problematic aggregates that may cause the self-collapse of hardened concrete or mortar, do X-ray fluorescence spectrum analysis test, put the aggregates with similar results to Fluorescence 1 together, crush and grind them and pass them through a 0.075mm square hole sieve to obtain Sample 2, do X-ray fluorescence spectrum analysis test, and record the result as Fluorescence 2; Step 4: Simulation test under specific environment; the specific process is as follows: Place the sheet or strip specimen that has been subjected to the X-ray fluorescence spectrometry test in a water bath and heat it to boiling. Keep boiling for 6 hours and then cool it naturally to room temperature. Observe the marking points and overall damage of the specimen after boiling, take photos and record them. After placing it in a natural drying state, perform the X-ray fluorescence spectrometry test on the material in the damaged point again, and record the result as fluorescence 0-0. Compare and analyze the relationship between fluorescence 0 and fluorescence 0-0, fluorescence 2 and fluorescence 1, fluorescence 0-0 and fluorescence 1, identify and find out the problematic aggregate that has not reacted, and record and analyze the self-collapse of aggregate at the identified point; Step 5: X-ray diffraction test; the specific process is: X-ray diffraction tests were conducted on sample 1 and sample 2, and the results were XRD1 and XRD2, respectively. The relationship between the two and the process of mutual transformation were analyzed; Step 6: Scanning electron microscope test; the specific process is as follows: Conduct SEM tests on the suspected reacted materials and unreacted suspected problematic aggregates at the collapse site to verify the X-ray diffraction analysis test results from the microscopic morphology; Step 7: Analysis of the impact of problematic aggregates; Step 8: Verify the handling and protection measures.

2. The method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates according to claim 1 is characterized in that The specific process of on-site sampling in step 1 above is as follows: The self-collapsed parts shall be sampled by core drilling or cutting. Before coring or cutting, the self-collapsed parts of hardened concrete or mortar shall be sealed and protected; and the granular or powdery suspicious materials in the self-collapsed parts shall be peeled off on site; the removed core samples or test blocks shall be marked and photographed.

3. The method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates according to claim 2, characterized in that The specific process of analyzing the impact of problematic aggregates in step 7 above is as follows: 16 core samples or test blocks were randomly selected, of which 10 core samples or test blocks were cut into two 10mm thick sheets or 10mm wide strips without appearance defects, a total of 20 test pieces, all of which were photographed for appearance; the remaining 6 core samples or test blocks were subjected to compressive strength tests, of which 3 were used as comparison test pieces; Put 3 core samples or test blocks and 20 test pieces into a water bath and heat them to boiling. Keep boiling for 6 hours and then cool them to room temperature naturally. After leaving them to dry naturally, test the compressive strength E0 of the test pieces and the compressive strength E0 of the test pieces respectively. Calculate the rate of change f of compressive strength before and after the test according to formula (1); conduct an appearance inspection and take photos, compare them with the photos before the test, count the number of damaged specimens X after boiling of 20 specimens, and calculate the self-collapse failure rate x caused by the problematic aggregate according to formula (2); the rate of change f of compressive strength before and after the test and the self-collapse failure rate x caused by the problematic aggregate are used as the basis for judging the degree of influence of the problematic aggregate on hardened concrete or mortar.

4. The method for detecting and analyzing the self-collapse of hardened concrete or mortar caused by problematic aggregates according to claim 3 is characterized in that The specific process of handling the verification of protective measures in step eight above is as follows: Take 18 core samples or strip test blocks from the core samples or test blocks retrieved from the site, put them into test box respectively, and place them in six environments for testing: naturally dry and isolated from air, naturally dry and in contact with air, moist surface and isolated from air, moist surface and in contact with air, saturated with water and isolated from air, and saturated with water and in contact with air, with 3 test pieces in each environment. Then put the test piece box into a water bath, raise the temperature from room temperature to 100±2℃, boil it for 6 hours, and then cool it naturally to room temperature. Check and record the damage of the test pieces in each environment, and judge which environment is most beneficial and most harmful to keeping the test pieces in good condition according to the damage of the test pieces, so as to give treatment and protection suggestions.

Citation Information

Patent Citations

  • Meso-fracture mechanical analysis method for high-volume rubber concrete

    CN111751188A

  • Method for determining content of cement and mineral powder in hardened concrete

    CN111751305A